Development of Student Worksheets on Dynamic Fluids Material to Enhance Scientific Creativity - Monica Maya Lusia; Suyidno Suyidno; Sarah Miriam; Dewi Dewantara (Universitas Lambung Mangkurat, 2024)
Scientific creativity involves creating innovative ideas, thoughts, or concepts. Scientific creativity in schools is not sufficiently trained. This study aims to produce valid, practical, and effective dynamic fluids student worksheets that are suitable for enhancing students' scientific creativity. This study applied the ADDIE model with 34 test subjects from the XI MIPA 3 class at SMA Negeri 8 Banjarmasin. Data were obtained from validation sheets, student response questionnaires, and learning outcome tests. The results showed that: (1) The student worksheets is considered valid because the validation results of the student worksheets and learning outcome tests were categorized as very good; (2) The student worksheets is considered practical because the results of the student response questionnaires were categorized as good; (3) The student worksheets is considered effective because the N-Gain of scientific creativity was 0.70, which falls into the high category. The developed dynamic fluids student worksheets is appropriate for enhancing students' scientific creativity in physics learning. Teachers can use this the student worksheets as an alternative to improve students' scientific creativity in physics education efforts.